Angiotensin Converting Enzyme Activity in Alopecia Areata. (1st October 2014) - Namazi, Mohammad Reza; Ashraf, Armaghan; Handjani, Farhad; Eftekhar, Ebrahim; Kalafi, Amir
Abstract : Background . Alopecia areata (AA) is a chronic inflammatory disease of the hair follicle. The exact pathogenesis of AA remains unknown, although recent studies support a T-cell mediated autoimmune process. On the other hand, some studies have proposed that the renin-angiotensin-aldosterone system (RAAS) may play a role in autoimmunity. Therefore, we assessed serum activity of angiotensin converting enzyme (ACE), a component of this system, in AA. Methods . ACE activity was measured in the sera of 19 patients with AA and 16 healthy control subjects. In addition, the relationship between severity and duration of the disease and ACE activity was evaluated. Results . Serum ACE activity was higher in the patient group (55.81 U/L) compared to the control group (46.41 U/L), but the difference was not statistically significant (P = 0.085 ). Also, there was no correlation between ACE activity and severity (P = 0.13 ) and duration of disease (P = 0.25 ) in the patient group. Conclusion . The increased serum ACE activity found in this study may demonstrate local involvement of the RAAS in the pathogenesis of AA. Assessment of ACE in a study with a larger sample size as well as in tissue samples is recommended in order to further evaluate the possible role of RAAS in AA.